The use of artificial intelligence combiners for modeling steel pitting risk and corrosion rate. (October 2017) - Chou, Jui-Sheng; Ngo, Ngoc-Tri; Chong, Wai K.
Abstract: Corrosion is a common deterioration that reduces the service life of concrete structures and steels. Particularly, corrosion behavior is a highly nonlinear problem influenced by complex characteristics. This study used advanced artificial intelligence (AI) techniques to predict pitting corrosion risk of steel reinforced concrete and marine corrosion rate of carbon steel. The AI-based models used for prediction included single and ensemble models constructed from four well-known machine learners including artificial neural networks (ANNs), support vector regression/machines (SVR/SVMs), classification and regression tree (CART), and linear regression (LR). Notably, a hybrid metaheuristic regression model was implemented by integrating a smart nature-inspired metaheuristic optimization algorithm ( i.e., smart firefly algorithm) with a least squares SVR. Prediction accuracy was evaluated using two real-world datasets. According to the comparison results, the hybrid metaheuristic regression model was better than the single and ensemble models in predicting the pitting corrosion risk (mean absolute percentage error=5.6%) and the marine corrosion rate (mean absolute percentage error = 1.26%). The hybrid metaheuristic regression model is a promising and practical methodology for real-time tracking of corrosion in steel rebar. Civil engineers can use the hybrid model to schedule maintenance process that leads to risk reduction of structure failure and maintenance cost. Graphical abstract: Highlights: Artificial intelligence is used in modeling the pitting risk and corrosion rate of steel. This study examines diverse novel prediction methods. The hybrid metaheuristic regression model has superior prediction accuracy. A scientific methodology for predicting pitting risk/corrosion rate in steel rebar.